2003
DOI: 10.1055/s-2003-45430
|View full text |Cite
|
Sign up to set email alerts
|

Obstructed Coarctation in a Right Aortic Arch in an Adult Female

Abstract: Coarctation of a right aortic arch is rare congenital anomaly. We report a rare case of a 24-year-old female with coarctation of the right aortic arch with aberrant left subclavian artery between the right common carotid and right subclavian arteries. The coarctation progressed into complete obstruction as the interruption of the aorta in adulthood. To prevent cerebral complications and progression to heart failure, surgical procedure was selected. Extraanatomical bypass grafting between the ascending and desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…These findings were seen in Case 1, which strongly suggested that adult type A IAA is the final stage of aortic coarctation degeneration. The IAA cases caused by severe CoA have also been reported in the literature[ 15 , 16 ]. The patients initially showed aorta narrowing.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were seen in Case 1, which strongly suggested that adult type A IAA is the final stage of aortic coarctation degeneration. The IAA cases caused by severe CoA have also been reported in the literature[ 15 , 16 ]. The patients initially showed aorta narrowing.…”
Section: Discussionmentioning
confidence: 99%
“…Patients diagnosed with interruption of the aortic arch in adulthood might be displaying progression of undiagnosed coarctation of aorta. Three-dimensional computed tomography is useful to detect the obstructive lesion and to guide the surgical approach [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Many cases may have a loss of luminal continuity between the ascending and descending aortic segments. Previous studies reported that the progression of the luminal stenosis may cause total occlusion of CoA [ 2 , 3 ]. CoA could be accompanied by patent ductus arteriosus (PDA), bicuspid aortic valve, and ventricular septal defect.…”
Section: Introductionmentioning
confidence: 99%